Analisis Penghambat Kemampuan Membaca Permulaan Pada Siswa Kelas II SD Negeri 054906 Tebasan Lama - Rizki Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
Abstract This study aims to identify and analyze factors that inhibit early reading ability in Grade II students of SD Negeri 054906 Tebasan Lama, and to describe teacher efforts in overcoming those barriers. A qualitative approach with a descriptive phenomenological design was used. Research subjects were 30 Grade II students, with the class teacher, parents, and school principal as additional informants. Data were collected through observation, semi-structured interviews, and documentation, analyzed using the Miles and Huberman model, and validated through source triangulation and member checking. Results revealed that: (1) 5 students (16.67%) experienced early reading barriers; (2) internal factors included physiological conditions (physical health, neurological ability, visual-auditory coordination) and psychological conditions (low motivation, lack of reading interest, and insufficient self-confidence); (3) external factors included limited parental accompaniment, unavailability of reading materials at home, inadequate literacy facilities, and insufficient variety in teaching methods; (4) teacher efforts such as routine reading practice, alphabetic and syllabic methods, and Level 2 graded readers with a word-pointing technique improved some students' reading fluency. This study concludes that early reading difficulties are multifactorial, requiring strong synergy among teachers, parents, and school through differentiated instruction, improved literacy resources, and sustained reading habits.